Deconstructing Bullying in Indonesian Animation: A Semiotic Analysis of Jumbo (2025) - Wa Ode Nur Aziza Rahmawati Elha; Muhammad Hidayatullah; Harry Fajar Maulana (Jogjakarta Communication Conference (JCC), 2026)
The film Jumbo (2025) presents a compelling portrayal of bullying through the experiences of the protagonist, Jumbo, a young elephant marginalized by his peers. This study aims to analyze the representation of bullying in Jumbo using Roland Barthes’ semiotic theory to explore how visual and narrative elements construct bullying behaviors, power dynamics, and moral messages. The research employs a qualitative, descriptive methodology, focusing on key scenes from the film. Through semiotic analysis, this study identifies the various forms of bullying depicted in the film—verbal, physical, and relational—and explores how the film critiques societal norms surrounding physical superiority. The findings highlight the transformative journey of Jumbo, whose personal growth challenges the normalization of bullying and promotes values of empathy, solidarity, and courage. By examining the ideological constructs embedded in the film, this research contributes to the understanding of how media, particularly animated films, can serve as powerful tools for social education and moral development. The study suggests that Jumbo offers important lessons for young audiences and calls for further research on the role of local animated films in addressing social issues in Indonesia.